Accuracy of Death Certificates in Attributing Mortality to Alzheimer’s Disease and Other Dementias in Japanese Psychiatric Hospitals - Sato K; Shioda K; Suda S (Neuropsychiatric Disease and Treatment)
Kengo Sato,1 Katsutoshi Shioda,1,2 Shiro Suda1 1Department of Psychiatry, Jichi Medical University, Tochigi, Japan; 2Cocoro Care Center, Jichi Medical University, Tochigi, JapanCorrespondence: Kengo Sato, Department of Psychiatry, Jichi Medical University, 3311-1 Yakushiji, Shimotsuke, Tochigi, 329-0498, Japan, Tel +81-285-58-7364, Fax +81-285-44-6198, Email tgv_thalys@hotmail.comAim: Dementia, including Alzheimer’s disease (AD), is a leading cause of mortality in Europe and the United States. Interestingly, while Japan is recognized for its high life expectancy, dementia-related diseases account for a comparatively lower proportion of recorded deaths. This study aimed to investigate the actual mortality attributed to clinically diagnosed AD in Japan, particularly in psychiatric hospital settings.Methods: Total 653 cases Death certificates and medical records from psychiatric hospitals in Japan were analyzed to investigate the actual death rate associated with dementia diseases.Results: In total, 134 of the 653 cases (20.5%) were determined to have AD as the direct cause of death, a significant increase from the 34 cases initially identified from death certificates alone (P< 0.01). And more, after reviewing the death certificates and medical records of 653 patients, 203 (134 with AD and 69 with other dementias) were identified as having dementia as the direct cause of death, representing 31.1% of all deaths. This rate was significantly higher than the rate identified before the medical record review (P< 0.01). Dementia diagnoses were frequently omitted from death certificates, with complications often recorded as the primary cause of death. This suggests that the true incidence of dementia-related mortality in Japan may be approximately four times higher than reported.Conclusion: We found that the true incidence of dementia-related mortality in Japan may be higher than reported. These findings underscore the critical need to increase awareness about dementia as a cause of death and to educate the public and healthcare professionals on accurately documenting it on death certificates.Keywords: Alzheimer’s disease, cause of death, death certificate, dementia diseases, Japan